2016
DOI: 10.3758/s13414-016-1244-y
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric interference in concurrent time-to-contact estimation: Cousin or twin of the psychological refractory period effect?

Abstract: In a reaction time (RT) task requiring fast responses to two stimuli presented close in time, human observers show a delayed RT to the second stimulus. This phenomenon has been attributed to a psychological refractory period (PRP). A similar asymmetric interference is found when performing multiple concurrent visual time-to-contact (TTC) estimations for moving objects, despite important differences between the tasks. In the present study, we studied the properties of the asymmetric interference found in the TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 56 publications
(78 reference statements)
2
11
0
Order By: Relevance
“…While temporal proximity is undoubtedly a key factor in the asymmetric pattern of error found when making two concurrent TTC estimations in the PM task, here we examined if there was also an influence of vertical separation between the two objects. Consistent with Baurès et al (2010Baurès et al ( , 2011Baurès et al ( , 2017, we found that temporal estimation was significantly more accurate for the lead object than the trail object. Extending upon previous work, we also found that the overestimation in CE for the trail object compared to the lead object was similar across a range of TTCs.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…While temporal proximity is undoubtedly a key factor in the asymmetric pattern of error found when making two concurrent TTC estimations in the PM task, here we examined if there was also an influence of vertical separation between the two objects. Consistent with Baurès et al (2010Baurès et al ( , 2011Baurès et al ( , 2017, we found that temporal estimation was significantly more accurate for the lead object than the trail object. Extending upon previous work, we also found that the overestimation in CE for the trail object compared to the lead object was similar across a range of TTCs.…”
Section: Discussionsupporting
confidence: 81%
“…Although the reference and distractor objects had identical visual features and an equal probability of moving at 5 or 7.5 deg/s in the upper or lower vertical location, TTC of the reference object was fixed at 1900 ms, whereas TTC of the distractor varied by ±250 ms or ±500 ms. Therefore, the pattern of CE described above and reported in previous work (Baurès et al, 2010;2017) could be specific to TTC of the reference object, which was constant across all trial types. To examine this issue, we repeated the same analysis on CE of the distractor object.…”
Section: Ce Distractor Objectsupporting
confidence: 51%
See 3 more Smart Citations